Assessing Respiratory Mechanics of Reverse-Triggered Breathing Cycles - Case Study of Two Mechanically Ventilated Patients. Issue 20 (2015) - Major, Vincent; Simon, Corbett; Redmond, Daniel; Beatson, Alex; Glassenbury, Daniel; Chiew, Yeong Shiong; Pretty, Christopher; Desaive, Thomas; Szlavecz, Akos; Benyo, Balazs; Shaw, Geoffrey M; Chase, J Geoffrey
Abstract: Mechanical ventilation patients may breathe spontaneously during ventilator supported breaths, altering airway pressure waveforms and hindering identification of true, underlying respiratory mechanics. This study aims to assess and identify respiratory mechanics for breathing cycles masked by spontaneous breathing (SB) effort using a pressure reconstruction method. The performance of the method is compared to parameters identified using a single-compartment model. Data from two patients (N=6305 breaths) experiencing SB and subsequent periods of muscle paralysis without SB were used for analysis. Patients are their own control and are assessed by breath-to-breath variation using coefficient of variation (CV) of respiratory elastance. Pressure reconstruction successfully estimates more consistent respiratory mechanics during SB by reducing CV up to 78% compared to conventional identification (p<0.05). Pressure reconstruction is comparable (p>0.05) to conventional identification during paralysis, and generally performs better as paralysis weakens (p<0.05). Pressure reconstruction provides less-affected pressure waveforms, ameliorating the effect of SB, resulting in more accurate respiratory mechanics identification.